2020
DOI: 10.21203/rs.3.rs-21553/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Codon Usage Pattern in SARS-CoV-2

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed significant threats to international health. The genetic traits as well as evolutionary processes in this novel coronavirus are not fully characterized, and their roles in viral pathogenesis are yet largely unknown. To get a better picture of the codon architecture of this newly emerging coronavirus, in this study we perform bioinformatic analysis, based on publicly available nucleo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The COVID-19 pandemic provided an unprecedented dataset of complete genomic sequences, with complete metadata including the sample collection date, which made possible the study of codon usage bias and its adaptation to the human host in short periods of time. First, using both maximum likelihood phylogeny and Correspondence Analysis (CA) of Average Codon Usage Frequencies (ACUF), we corroborated that SARS-CoV-2 is highly related to the SARS-related coronavirus RatG13 isolated from Bats, and to Pangolin CoV [45, 47], being more distantly related to SARS-CoV and MERS-CoV. In addition, the CA showed that SARS-CoV-2 was farther from the human tissues than SARS-CoV and MERS-CoV, suggesting that it is less adapted than the latter for protein expression in the human host.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The COVID-19 pandemic provided an unprecedented dataset of complete genomic sequences, with complete metadata including the sample collection date, which made possible the study of codon usage bias and its adaptation to the human host in short periods of time. First, using both maximum likelihood phylogeny and Correspondence Analysis (CA) of Average Codon Usage Frequencies (ACUF), we corroborated that SARS-CoV-2 is highly related to the SARS-related coronavirus RatG13 isolated from Bats, and to Pangolin CoV [45, 47], being more distantly related to SARS-CoV and MERS-CoV. In addition, the CA showed that SARS-CoV-2 was farther from the human tissues than SARS-CoV and MERS-CoV, suggesting that it is less adapted than the latter for protein expression in the human host.…”
Section: Discussionmentioning
confidence: 73%
“…Further, for SARS-CoV-2, different results were reported, indicating from a main role of mutational pressure, to a strict selection pressure [33,[36][37][38]. In the case of human coronaviruses, including SARS-CoV, MERS-CoV and SARS-CoV-2, several CUB analyses were carried out [26,33,[43][44][45][46][47][48][49][35][36][37][38][39][40][41][42]. As a result, some general conclusions could be made: first, all of them possessed high AU content and low GC content, with the CpG dinucleotide markedly under-represented, and in the case of SARS-CoV-2, a preferred use of U-ending codons; codon usage bias and codon pair usage were found to be quite different from that of the human host, even when particular tissues such as lung and kidneys were analyzed [50]; high Effective Number of Codons (ENC) [51] values were found (although lower than those of other coronaviruses), suggesting a slight codon usage bias; in comparison to other coronaviruses, SARS-CoV, MERS-CoV, and SARS-CoV-2 presented the highest values of the Codon Adaptation Index (CAI) [52] calculated using human proteins as the reference set, suggesting that these viruses are more adapted to the human host than other coronaviruses that present milder clinical symptoms; a relatively high average CAI value was found for SARS-CoV-2 (approximately 0.7), however, its value was smaller than the average for human genes (approximately 0.8) [44].…”
Section: Introductionmentioning
confidence: 99%
“…This low codon usage bias could potentially facilitate spillover events involving SARS-CoV-2 since the virus would still be able to replicate efficiently in a new host (Kandeel et al, 2020). A Relative Synonymous Codon Usage (RSCU) analysis for SARS-CoV-2 sequences showed that the majority of the over-represented codons (>1.6) ended with A/U while the majority of the under-represented codons (<0.6) ended with G/C (Hou, 2020). Similar results were seen in our analysis of EHDV and Cervid atadenovirus A.…”
Section: Mainmentioning
confidence: 99%
“…From another viewpoint, the RSCU pattern across the Algerian and the reference genomes were very similar with slight differences regarding the values in all genes, in addition to a preference for U-ending codons in the overrepresented codons. Once more, as per anterior reported studies regarding the SARS-CoV-2 codon usage, the pattern is more or less conserved independently from the geographical provenance [18,19]. Globally, the ω ratio across all genes was often times either impossible to calculate (ka=ks=0) or had extreme values (∞ when ks=0 and 0 when ka=0), of which is due to insufficient nucleotide variations characteristic in the early phase of the pandemic [12,20].…”
Section: Discussionmentioning
confidence: 72%